그림책화면에서 나타나는 은유적 표현방식에 대한 어린이의 인지반응연구 - 유동관(Dong-Kwan Yoo) (한국콘텐츠학회 논문지, 10(7), 2010)
Formation of optical meaning shown in the picture book screen is the original expression method in that it makes you understand properties or characteristics of subjects more easily and faster adding another images to them, exaggerating or reducing them as well as shows the phenomenon that you try to deliver. In this study, I first prepared the framework of classification on metaphorical expression methods of the picture books' illustration through theoretical study on the optical metaphorical characteristics and expression forms to analyze how the metaphorical expression methods shown in the picture books for children works optically and psychologically to them. Also, I divided the expression form into 2 types to derive optical psychological perceptional response of children through the empirical survey and analyzed linguistic psychological response of children by type utilizing it as the survey materials of in-depth interviews. Finally, I think that the result of this study will help screen production based on personality and creativity of illustrators and, in addition, it will be utilized in studies and tests of the effective expression methods for students who learn illustration. 그림책화면에서 나타나는 시각적 의미형성은 전달하고자 하는 현상이나 메시지를 직접적으로 보여주는 것뿐만 아니라 다른 이미지를 더하거나 과장, 축소하여 대상의 속성이나 특성을 보다 쉽고 빠르게 이해시켜줄 수 있다는 점에서 독창적인 표현방법이 된다. 본 연구는 어린이그림책에서 나타나는 은유적 표현방식이 어린이에게 시각적 심리적으로 어떻게 작용하는지 분석하기 위하여 먼저, 시각적 은유특성과 표현형식에 대한 이론적 고찰을 통해 그림책일러스트레이션의 표현방법에 대한 범주화의 틀을 마련하였다. 또한 실증조사를 통해 어린이의 시각적 심리적 지각반응을 명확하게 도출하기 위하여 표현형식을 2가지 유형으로 구분하고, 이를 심층면접의 설문자료로 활용하여 유형별 어린이의 언어적 심리적 반응을 분석하였다. 끝으로 본 연구가 제시한 결론은 일러스트레이터의 개성과 창의성이 바탕이 된 화면제작에 도움이 됨은 물론, 일러스트레이션을 배우는 학생들에게 효과적인 표현방법연구와 실험에 활용될 것으로 사료된다.